Fabrication and characterization of masterbatches made from poly(vinyl chloride) and modified fly ash - Tham, Do Quang; Thu Trang, Nguyen Thi; Chinh, Nguyen Thuy; Mai, Tran Thi; Giang, Nguyen Vu; Kim Dung, Nguyen Thi; Hoang, Thai (Vietnam Journal of Chemistry, 2016)
Masterbatches made from plasticized poly(vinyl chloride) (PVC compound) and modified fly ash by stearic acid (MFA) or unmodified fly ash (FA) were fabricated by extrusion method  using a twin-screw extruder. The relative melt viscosity, tensile properties, dielectric properties and flame retardance of the masterbatches were characterized by using Haake Rheomix 9000 (Germany), tensile measurement (Zwick I V2.5, Germany), dielectric measurement (Aglient instruments model E4980A, USA) and vertical burning test (as per UL 94, USA), respectively. The results indicate that FA increase the viscosity of PVC compound, while MFA significantly reduces the viscosity of PVC compound. It means that modification of FA by stearic acid is an advantage way for improving the processability of the PVC- filler masterbatches. Young’s modulus of PVC/FA and PVC/MFA masterbatches increases as increasing filler content. However, tensile strength and elongation at break of the masterbatches strongly reduce due to high filler content. Fortunately, there is a slightly enhancement effect on the tensile strength and elongation at break when using MFA instead of original FA. The density of the masterbathches is increased as function of filler content. It is interesting to know that the dielectric constant of PVC/FA and PVC/MFA masterbatches is propotional to the FA and MFA content. The flame retardance of PVC/FA and PVC/MFA masterbatches is classified as V-0 and V-1 rating in UL VB 94 test. Keywords. Modified fly ash, masterbatch, PVC, processability, dielectric, flame retardance.